Penyuluhan Ergonomi Aktivitas pada Pasien Low Back Pain Di RSUD Dr. Iskak Tulungagung (Health Care : Journal of Community Service, 2025)
Low Back Pain (LBP) is a common complaint often caused by non-ergonomic sitting postures. Factors causing LBP include individual factors such as age, gender, and length of service, as well as occupational factors such as static body positions, repetitive movements, and excessive force exertion. This condition can lead to decreased productivity due to lost work time. This study aims to increase the elderly's understanding of the symptoms and causes of LBP and provide education regarding independent home exercises as a preventative measure. Work requires an ergonomic work position, because non-ergonomic work postures can increase the likelihood of musculoskeletal disorders (MSDs). These musculoskeletal disorders can reduce worker productivity, cause longer production times and increase worker absenteeism. Understanding ergonomic work positions is crucial for workers. Physiotherapy, as a health service that focuses on the development, maintenance, and recovery of body parts due to physical disorders, can help prevent musculoskeletal problems by utilizing ergonomic principles. Before starting the counseling, researchers filled out a questionnaire or pre-test with patients and after the counseling, a post-test was administered. The results of the counseling obtained based on the pre-test and post-test showed a 100% increase in understanding of educational material related to ergonomic work postures and stretching exercises.